The Occurrence of Valvular Atrial Fibrillation: Involvement of NGF/TrKA Signaling Pathway. Issue 12 (26th November 2021) - Wang, Qianli; Zhao, Yong; Dong, Xin; Li, Cong; Zhou, Lin; Zou, Chengwei; Li, Xiaodong; Zhou, Nannan; Liu, Junni; Sun, Yuanyuan; Wang, Jianchun
Abstract: Objective: Nerve growth factor (NGF) and tropomyosin kinase receptors A (TrKA) exert a crucial effect on the regulation of autonomic nervous system which contributes to the progress of atrial fibrillation (AF). Valvular heart disease (VHD) patients are more easily to induce the AF. We investigated whether NGF/TrKA could impact the occurrence of AF in VHD patients. Materials and methods: Atrial tissues were resected from 30 VHD patients with chronic AF ( n = 15, AF >6 months) or sinus rhythm (SR, n = 15). The expression of NGF, TrKA, protein kinase B (PKB/Akt), beta-isoforms of glycogen synthase kinase-3 (GSK3β), Serine473 phosphorylation of Akt (p-Ser473 Akt), Serine9 phosphorylation of GSK-3β (p-Ser9 GSK3β) in right atrial tissues and peripheral blood lymphocyte were quantified by Western blot. The localization of those genes expression was measured by immunohistochemistry. Double sandwich enzyme-linked immunosorbent assay was used to observe the trace changes of NGF-β in peripheral plasma. Results: Our results revealed that the NGF expression was markedly elevated in the tissue of right atrial appendage and peripheral blood lymphocytes from AF patients compared with the SR patients. But, the expression of TrKA, GSK3β, p-Akt and p-GSK3β were decreased. There was no difference about the expression of Akt from the AF patients and the SR patients. The NGF-β level in peripheral blood plasma of patients with AF and SR was not statistical difference. Conclusion: Thus, we thought that NGF/TrKA signaling pathway may be involved in the AF in the patients with VHD, inactivation of GSK3β could increase the incidence of AF, but not relevant to phosphorylation.